The analysis of contexts of coping with stress, experienced by social welfare professionals: experience of Lithuania and Scandinavian countries - Alifanovienė, Daiva; Šapelytė, Odeta; Gerulaitis, Darius (Social Welfare: Interdisciplinary Approach, 2017)
The article deals with stress and coping with the stress experienced by social welfare professionals in different social and cultural context. The comparison of inter-professional stressogenity shows that the greatest stress is experienced by the representatives of social sphere professions. The main aim of the article is to disclose the contexts of possibilities for coping with stress experienced by social welfare professionals in Lithuania and Scandinavian countries. Specialists’ (N=12) experience was analysed employing the qualitative data collection method (semi-structured written interview), using  open-ended questions according to assessment areas foreseen by the researchers. Reconstructing the context of coping with stress experienced by specialists of social welfare professions of these countries, certain differences showed up: Lithuanian social welfare professionals use the most affordable ways for stress coping in the intrapersonal (physical and emotional) area. Due to a more favourable socio-economic situation in the country, Scandinavian informants have a wider range of stress management possibilities in terms of affordability, content and choice.
Keywords: Contexts of Coping with the Stress; Social Welfare Professionals; Intrapersonal – Interpersonal Stress Level